Poly(epsilon-caprolactone) nanocapsules carrying the herbicide atrazine: effect of chitosan-coating agent on physico-chemical stability and herbicide release profile - Grillo, R. [UNESP]; Rosa, A. H. [UNESP]; Fraceto, L. F. [UNESP] (Springer, 2014)
Polymeric nanoparticles can be used as carrier systems for a variety of bioactive compounds, altering the physico-chemical properties of the substances that are incorporated in the particle matrix. Coating techniques are employed to modify the interactions of the particles with the target medium. The objective of this work was to prepare nanocapsules of poly(epsilon-caprolactone) containing the herbicide atrazine and study the effect of coating the nanocapsule surfaces using different concentrations of chitosan. The encapsulation efficiency, release kinetics profile, and physico-chemical stability of the formulations were evaluated. Encapsulation percentages of 64-84 % were achieved. The release kinetics profile of the herbicide was altered when the nanocapsules were coated, and the release mechanism could be described by a combination of diffusion and relaxation of the polymeric chains. The stability of the formulations was influenced by the concentration of chitosan used in the preparation procedure. Given the global application of herbicides in agriculture, the results indicate that their association with coated modified release carrier systems could be beneficial from both ecological and economic perspectives. These systems offer delivery that is more efficient, as well as improved adhesion of herbicides to the target plants.
Keywords: Environmental chemistry; Atrazine; Coated polymeric nanoparticles; Chitosan